1992
DOI: 10.1093/bja/68.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Posture, Phonation and Observer on Mallampati Classification

Abstract: We have studied the effects of phonation and posture on the Mallampati classification of view of the pharyngeal structures. Differences between observers were allowed for by the experimental design and log-linear modelling. Sixty-four patients were assessed on the ward, sitting upright, with and without phonation, by each of two observers. Another 64 patients were assessed without phonation, but both upright and supine, again by both observers. Phonation (the patient saying "Ah") produced a marked, systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 9 publications
1
46
2
Order By: Relevance
“…THAM et al [20] observed that posture had a very small effect on the MS in a group of 128 subjects. Supine position displaced the distribution of the MS slightly towards the higher classes of Mallampati.…”
Section: Discussionmentioning
confidence: 98%
“…THAM et al [20] observed that posture had a very small effect on the MS in a group of 128 subjects. Supine position displaced the distribution of the MS slightly towards the higher classes of Mallampati.…”
Section: Discussionmentioning
confidence: 98%
“…The classical Mallampati test is done in the sitting patient, with his/her head in the neutral position. However, when performed in the supine position, the test may have a higher positive predictive value and is associated with more true positives than assessment in the sitting position [10][11][12] . The specificity and positive predictive value of the MMT can be improved when performed in the sitting patient with extension of the craniocervical junction 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen (36%) patients in Gr-A faced difficulties during intubation, which is significantly higher than the Gr-B (p =0.001). 10 . One of the greatest criticisms of mallampati test, however, has been the problem of inter-observer variation 9 .…”
Section: Resultsmentioning
confidence: 99%